1986
DOI: 10.1002/jmv.1890200207
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Internalization of Herpes Simplex Virus‐Antibody Complexes by Polymorphonuclear Leukocytes

Abstract: We studied the interactions between rabbit polymorphonuclear leukocytes (PMN) and the RE strain of herpes simplex virus type 1 (HSV-1) to determine better the role of inflammatory cells in herpetic stromal keratitis. PMN were found to be nonpermissive for HSV replication and were unable to bind virus in the absence of antibody. However, PMN did bind and internalize HSV-antibody complexes in vitro as was demonstrated visually by electron microscopic studies and quantitatively by measurement of activity associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…We calculated, using both quenching with trypan blue and the ammonium chloride assay, that 80% of the viruses are inside the cell. This complement enhancement of antibody-dependent phagocytosis was also reported by Smith et al (2), and may be due to the formation of larger immune complexes or a more efficient adhesion to the PMN, because more receptors are involved. This enhanced adhesion will lead to enhanced internalization because the PMN is triggered by Fc receptors.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We calculated, using both quenching with trypan blue and the ammonium chloride assay, that 80% of the viruses are inside the cell. This complement enhancement of antibody-dependent phagocytosis was also reported by Smith et al (2), and may be due to the formation of larger immune complexes or a more efficient adhesion to the PMN, because more receptors are involved. This enhanced adhesion will lead to enhanced internalization because the PMN is triggered by Fc receptors.…”
Section: Discussionsupporting
confidence: 83%
“…Recently it has been shown that phagocytes can ingest and kill virions and methods have been developed to measure the uptake of these virions using either radiolabeled techniques (1)(2)(3) or chemiluminescence (4)(5)(6). The role of this phenomenon in vivo is shown by experiments with influenza virus and foot and mouth disease virus in a murine model (1,5,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have shown that PMN are able to bind to virus infected cells [9,16,27] and to internalize virus particles [23]. Although granulocytes are able to lyse HSV-infected cells in vitro, the high effector to target ratios and the long incubation periods required cast some doubt on the role of this process in vivo [14,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…For herpes simplex virus (HSV) the role of phagocytosis by polymorphonuclear leukocytes (PMN), at least in keratitis, seems to be established (Smith et al, 1986;Bingham et al, 1985). We (Van Strijp et al, 1989a,b) and others (Bingham et al, 1985;Fujisawa et aL, 1987;McCullough et al, 1988;Smith et al, 1986;West et al, 1987) have shown that viruses, including HSV, are efficiently phagocytosed by PMN and monocytes (MN). However, the importance of phagocytosis in antiviral defence can not be limited to the phenomenon of uptake alone.…”
mentioning
confidence: 99%